Exploring the Impact of Mental Health on University Students' Behavior and Attitudes Towards Crime Prevention - Alkhawaldeh, Areen Mohammed Alghzewat; Alkrimeen, Ayman Ahmad (Journal of Ecohumanism, 2024)
The objective of the research was to find out how mental health affects the behavior and crime prevention attitudes of university students. A sample of 300 university students from various academic backgrounds and demographic factors was taken for the study. A self-administered survey questionnaire comprising 30 items on mental health, crime prevention, police, and behavioral orientations was used for data collection. The method employed descriptive statistical indices like the mean, standard deviation, and p-value to measure the relationship between the attitudes and behaviors of students regarding crime prevention and mental health. The results indicated that students reported, on average, moderate anxiety (mean = 3.6, SD = 1.1), sadness (mean = 3.5, SD = 1.2), and stress (mean = 3.7, SD = 1.0). Students' satisfaction with the university's mental health services was 3.4 (SD = 1.1). Most students also utilized mental health support, with a mean of 2.9 (SD = 1.3). There was an almost complete agreement regarding crime prevention programs, as indicated by a mean score of 3.9 (SD = 1.1), regarding how important it is to include mental health services in these programs. Students who were diagnosed with mental illness felt more strongly that criminal action was justified (mean = 2.9, SD = 1.3) and believed more strongly in restorative justice as opposed to punitive measures (mean = 3.7, SD = 1.2). Overall, the findings indicate that mental health is a significant factor in students' behavior and attitudes regarding crime prevention, and universities should include mental health services in crime prevention initiatives aimed at promoting student well-being and deterring criminal activity.